Effects of 4-hydroxy-2,5-dimethyl-3(2H)-furanone supplementation on growth performance, serum antioxidant capacity, rumen fermentation characteristics, rumen bacterial quorum sensing, and microbial community in Hu sheep - Chuanpei Fu; Jing Ge; Mingren Qu; Kehui Ouyang; Qinghua Qiu (Animal Bioscience, 2025)
Objective This study aimed to investigate the effects of 4-hydroxy-2,5-dimethyl-3(2H)-furanone (HDMF) on growth performance, serum antioxidant capacity, rumen fermentation characteristics, rumen microbial LuxS/AI-2 quorum sensing, and community composition in Hu sheep. Methods Twenty-two male Hu sheep with similar body weights (19.97±0.41 kg) and ages (66.75±2.11 days) were evenly divided into two groups: the control group, receiving a basal diet (n = 11, CON), and the treatment group, receiving the basal diet supplemented with an additional 1.0 g/d of HDMF (n = 11, HDMF). Results The results showed no significant differences in average daily gain, average daily dry matter intake, and feed conversion ratio between the HDMF and CON groups (p>0.05), but numerical improvements of 11.12%, 4.55%, and 7.56% were observed, respectively. Compared to the CON group, the HDMF group exhibited elevated levels of serum glutathione peroxidase and superoxide dismutase, and decreased levels of malondialdehyde and reactive oxygen species, as well as a reduced oxidative stress index (p<0.05). Dietary HDMF supplementation did not affect rumen fermentation characteristics, except for the proportion of valerate (p<0.05). HDMF supplementation increased the AI-2 signaling molecules concentration and biofilm formation in the rumen fluid (p<0.05). No substantial differences were seen in the richness and evenness of rumen microbes between the HDMF and CON groups. Principal coordinates analysis and nonmetric multidimensional scaling analyses revealed an obvious overlap between the two groups, and analysis of similarities also indicated no significant differences (R = 0.0116, p = 0.303). Subsequent species annotation and biomarker analysis revealed that the HDMF group reduced the abundances of Shuttleworthia, Eubacterium eligens group, and Erysipelotrichaceae UCG 002, and increased the abundances of Riknellaceae RC9 gut group, Prevotellaceae UCG 003, Desulfobulbus, Methanobrevibacter, and Selenomonas ruminantium. Conclusion This study indicates that HDMF supplementation enhances the body’s antioxidant capacity and increases the abundances of certain disease-resistant bacteria by promoting AI-2 signaling molecules and biofilm formation, thereby ultimately contributing to the enhanced growth performance of Hu sheep.